A Rape Law Pedagogy - Bloch, Kate E (2015)
Teaching rape law can be a little like the descent from the Castle at Chich6n Itzi. The angle of descent is so steep and the steps so narrow that, from the edge of the platform, you can barely see the stair onto which you will next descend. For some, the descent is a challenge: a test of will, balance, and belief. For others, each step of the descent embodies a small, heartstopping leap of faith. Fortunately, at Chich6n Itzdi, some kind stairway reconstructionist has installed a metal-linked chain secured directly to the steps.3 This metal guide enables one, if one is willing to proceed in a somewhat awkward pose, to descend from the platform to the ground with a sense of substantially enhanced security. Not only does the chain make for a more comfortable passage, but I suspect that knowledge of its existence would encourage some otherwise hesitant souls to undertake the ascent